On Minimizing Risk and Harm in the Use of Psychedelics - Jules Evans; Marc Aixalà; Brian T. Anderson; William Brennan; Rebecka Bremler; Joost J. Breeksema; Lisa Burback; Abigail E. Calder; Robin L. Carhart‐Harris; Katherine Cheung; Neşe Devenot; Ingmar Gorman; et al. (Psychiatric Research and Clinical Practice)
Objective This article outlines recommendations from 30 psychedelic researchers on how to create a better psychedelic safety net. Methods A survey of 30 psychedelic researchers asked them to identify key critical research gaps around psychedelic harm and safety. Results The critical research gaps identified by the authors included defining the main types of psychedelic harm, the predictors of those harms, and the most effective way to treat those harms. They also call for better support for those experiencing post‐psychedelic difficulties, including better online information, peer support groups, affordable therapy, and psychiatric consultation and medication. Finally, the authors call for better funding to create a psychedelic safety net, and suggest psychedelic philanthropists, investors and companies could commit 1% of their investment in psychedelics into supporting safety measures such as research and support services. Conclusions The authors identify several practical steps to create a better psychedelic safety net and call for more funding to psychedelic safety measures such as research and support services. Relevance to clinical practice The authors outline important gaps in our knowledge around the safety and risk profile of psychedelic medicines and identify practical steps forward for researchers and clinical practitioners to make this promising field safer.